Evaluation des paramètres de reproduction d’un cheptel ovin de la race Rembi. - Bouchikhi, Yacine. (My University, 2018)
This study is a contribution to assessing the reproductive potential of Rembi ewes. The good control of reproductive parameters of this race allows for better productivity. In the first part, the reproduction is influenced by various external factors represented the environment, food, the method and the control and internal time represented by the genetic potential. In part, it was conducting a detailed study of the demonstration farm and sheep population is existing, thus evoking the main agents that regulate reproduction in order to make a statement. In the last part we evaluate reproductive parameters represented by fertility fertility, prolificacy and mortality ageneax from data collected on livestock, then we analyze the state of places, finally we try to meet the constraints and that in view of developing production.
Keywords: Rembi; lutte; ovin; fertilité; prolificité.; fécondité; fight; sheep; fertility; prolificacy; fertility